“Well, to be honest, I don’t have an idea of what it might be": a qualitative study on knowledge and awareness regarding nonmelanoma skin cancer - Brokmeier, Luisa Leonie; Diehl, Katharina; Spähn, Bianca Annika; Jansen, Charlotte Elisabeth; Konkel, Tobias; Uter, Wolfgang; Görig, Tatiana (Current oncology, 2023)
Nonmelanoma skin cancer (NMSC) is the most common cancer type in Western industrialized countries. However, research into the knowledge and awareness in the general population regarding NMSC is still scarce. This qualitative study aims to fill this research gap. Face-to-face, semi-structured interviews with 20 individuals aged 55-85 years were conducted between February and October 2020. Transcribed interviews were analyzed using qualitative content analysis. The term “white skin cancer”—the German colloquial term of NMSC—was well-known, but the incidence was underestimated. None of the participants could give a precise definition of NMSC, and various alterations in the skin were, partially wrongly, stated as potential signs for NMSC. As risk factors for NMSC, solar radiation, and fair skin type were mentioned most often. The perceived individual risk of developing NMSC and risk compared to individuals of the same age and gender were low in our sample. Own knowledge about NMSC was mostly perceived to be insufficient, and the majority of the sample would like to receive more information on NMSC. Our results emphasize a need to inform about the signs and risks of NMSC not only in the studied older age group but also in younger people.
Gesehen am 18.07.2024